Sam the man & the rutabaga plan - Dowell, Frances O'Roark (Dowell, Frances O'Roark. Sam the man, 2017)
"Sam the Man is not a vegetable man. But when a school project has him paired up with the worst of all the vegetables--the rutabaga--he soon will learn that it's not half bad. And as he grows fond of his new little friend, Sam the Man will have to come up with a plan on how to keep him happy before he rots!"--